Analysis of 'Urf in Practices and Ethics in E-Commerce Transactions - Hidayat, Febryan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose and Methodology: This research examines the role of 'urf (social customs) in shaping e-commerce business practices, focusing on three dimensions: the marketplace contract of sale (ijab qobul), the cost of return shipping, and the practices of affiliates requesting product samples in affiliate marketing. The aim of the research is to investigate the role of 'urf in e-commerce business practices, using a qualitative method with a library research approach. Results: In the dimension of the contract of sale (ijab qobul), 'urf plays an important role in describing the changing transaction patterns from offline to online. Although the contract of sale is often not expressed verbally or in writing, the 'urf remains the legitimate basis according to Sharia principles. In the dimension of return shipping costs, 'urf serves as the basis for fair business practices in accordance with Sharia principles. Sellers responsible for shipping errors bear the cost of return shipping, reflecting good 'urf and adherence to Islamic business ethics. Finally, in the practice of affiliates requesting product samples, 'urf as a common habit of affiliates poses challenges in terms of safety and fairness in marketing. This research highlights the importance of understanding 'urf and reaching early agreements between stakeholders to prevent unethical practices. In conclusion, 'urf not only reflects societal customs, but also becomes a critical point in formulating business practices that are in line with the ethics and principles of Islamic Shari'ah, providing guidance for e-commerce companies to adopt practices that are more ethical and fair.